Escola Agrotécnica Federal de Urutaí (1978-1986): a formação de mão de obra agrícola no Sudeste Goiano - Issa, Silvia Aparecida Caixeta (2018)
The agrotechnical schools, coordinated by the Coagri, implemented the School-Farm System, a methodology that combined education, work and production; with specific physical structure equipped with: classrooms, educational units of production and cooperative-school. There is no work on the history of the Federal Agrotechnical School of Urutaí (EAFUR 1978-1986) permeated by the influence of agricultural development in Brazil and Goiás, in the period in which it was coordinated by the Coagri. The initial hypothesis is that Coetagri fulfilled its role in the training of Agricultural Technicians and the implementation of an agricultural school culture in the different pedagogical and work activities developed in the educational institution. The research sought to analyze the institutional structure and the training practices developed in the School, configured by economic and productive relations inserted in the regional context and in the development policy of agriculture and livestock in the country and Goiás in the period between the years 1978-1986, and to discuss the school culture produced by the institution that implemented the School-Farm System and promoted an agricultural school culture in its different spaces, through its pedagogical actions and the school community. The theoretical support included the contributions of Magalhães (2004), Escolano (2000, 2017), Viñao Frago (1995, 2006), Escolano and Viñao Frago (1998), Goodson (1997, 2013) and Chervel (1990). The methodology used to track EAFUR was built by analyzing school documents (minutes, letters, school diaries, tuition and diploma registration books, maps, building plans, work plans, regulations, regiments, reports, crafts, service orders, which were located in the institution and compared with COAGRI documents (handouts, report cards, guidelines, advertising inserts, regulations, regiments) and the Ministry of Education and Culture (MEC). It is also had the participation of former employees who contributed giving explanations to understand the period analyzed. After reading and analyzing the sources, it was concluded that the initial hypothesis was confirmed, in other words, that the EAFUR developed an agricultural school culture in the different pedagogical activities, in the promotion and development of projects both in the agricultural and animal husbandry sectors. Although it had subsidies, it needed to be produced to receive them, and with that, it developed an institutional culture shaped in the economic and productive relations inserted in the context of the policy of development of agriculture and cattle raising in Brazil and Goiás. The aim of this study was to show the agricultural school culture developed at EAFUR, an institution that had as its purpose the training of Agricultural Technicians and who fulfilled its attribution through the interaction between external dictates and internal projections.